2012
DOI: 10.3163/1536-5050.100.4.008
|View full text |Cite
|
Sign up to set email alerts
|

Is literature search training for medical students and residents effective? a literature review

Abstract: Although the findings of most of the studies indicate that the current instructional methods are effective, the study designs are generally weak, there is little evidence that learning persists over time, and few validated methods of skill measurement have been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
(33 reference statements)
4
28
0
4
Order By: Relevance
“…This integration has ensured that all incoming interns and residents are given an introduction to library services and resources, and that they're able to build on the foundation of evidence-based medicine and a spirit of inquiry and lifelong learning established in medical school. Moreover, the practice is consistent with the current trend towards more embedded library instruction (Just, 2012).…”
Section: Providence Portland Medical Center Internal Medicine Residensupporting
confidence: 65%
“…This integration has ensured that all incoming interns and residents are given an introduction to library services and resources, and that they're able to build on the foundation of evidence-based medicine and a spirit of inquiry and lifelong learning established in medical school. Moreover, the practice is consistent with the current trend towards more embedded library instruction (Just, 2012).…”
Section: Providence Portland Medical Center Internal Medicine Residensupporting
confidence: 65%
“…The Berlin and Fresno tests are often mentioned as valid EBM tests, but were unfortunately not applicable to this study. The Berlin test [3,10] does not include assessment of skills, such as literature searching, and the Fresno test [11] is very demanding in time and resources. The EPIC scale [12] only has one question about the perceived ability to conduct a literature search, whereas the ACE tool [13] asks four questions about the PICO question and search strategy for a given patient scenario.…”
Section: How Is Ebm Assessed?mentioning
confidence: 99%
“…One common thread across many of the articles surveyed is that very few studies tested participants after a significant amount of time had elapsed after their EBM training. Gruppen et al [4] and Just [3] both recommended that more research is needed to examine the long-term retention of skills. Dorsch et al [5] concluded that medical graduates who were trained in their undergraduate program "retained EBM skills in residency and maintained a positive attitude about the importance of applying EBM principles to patient care."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on database training for medical students suggests that librarian-led trainings can be effective at improving the evidence based literature searching skills of medical students. The literature reveals that much of this evidence, pointing to a positive effect, comes from studies with weak designs (Garg & Turtle, 2003;Just, 2012;Maggio & Kung, 2014). A rigorously designed double blind clinical trial did not find any effect on medical student search skills following a single training session (Ilic, Tepper, & Misso, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%